Strategies that occupational therapists in the public health sector in KwaZulu-Natal use to navigate language discordance: a qualitative descriptive study - Marshall, Emily (Department of Health and Rehabilitation Sciences, 2022)
Background: Language discordance, a challenge of miscommunication between health professionals and service users, is a concern for occupational therapy, a profession that foregrounds a client-centred partnership. Occupational therapy literature highlights language discordance as one of the biggest challenges encountered when working in the rural public health sector. Language discordance affects the quality of health services which results in misdiagnosis, informed consent violations, decreased service user satisfaction and safety risks, among others. Occupational therapy is not immune to these negative consequences. In a country as linguistically diverse as South Africa, the need to find effective ways to navigate language discordance in occupational therapy health care, is crucial. However, there is limited literature on language discordance and the strategies used to resolve the issue. Aim: The aim of this study was to describe strategies that occupational therapists working in the public health sector in KwaZulu-Natal use to navigate language discordance and to understand the subsequent role that language discordance has on the quality of occupational therapy care. Methodology: The study adopted a qualitative descriptive design using semi-structured interviews with eight participants recruited using purposive and snowball sampling. Thematic analysis was used to analyse data. Findings: Four themes emerged, namely; using various communication strategies concurrently, language definitely impacts that therapy process, factors perpetuating language discordance and I'm doing everything that I can, what more can I do? Conclusion: The impact of language discordance on the quality of occupational therapy care is undeniable. However, the participants showed agency in navigating language discordance using personal and institutional resources amidst the complexities of applying various strategies concurrently in order to provide the best care that they could.